Aspidospermatan-aspidospermatan and eburnane-sarpagine bisindole alkaloids from Leuconotis - Gan, Chew Yan; Low, Yun Yee; Robinson, W.T.; Komiyama, K.; Kam, Toh Seok (Elsevier, 2010)
Leucofoline and leuconoline, representing the first members of the aspidospermatan-aspidospermatan and eburnane-sarpagine subclasses of the bisindole alkaloids, respectively, were isolated from the Malayan Leuconotis griffithii. The structures of these bisindole alkaloids were established using NMR and MS analysis, and in the case of leuconoline, confirmed by X-ray diffraction analysis. Both alkaloids showed weak cytotoxicity towards human KB cells. (C) 2010 Elsevier Ltd. All rights reserved.